qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = 0$
$y = \dfrac { 3 } { 4 } x + 3$
$x$Intercept
$\left ( - 4 , 0 \right )$
$y$Intercept
$\left ( 0 , 3 \right )$
$0 = \dfrac{ 3 }{ 4 } x+3$
$x = - 4$
$ $ Solve a solution to $ x$
$0 = \color{#FF6800}{ \dfrac { 3 } { 4 } } \color{#FF6800}{ x } + 3$
$ $ Calculate the multiplication expression $ $
$0 = \color{#FF6800}{ \dfrac { 3 x } { 4 } } + 3$
$\color{#FF6800}{ 0 } = \color{#FF6800}{ \dfrac { 3 x } { 4 } } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$ $ Multiply both sides by the least common multiple for the denominators to eliminate the fraction $ $
$\color{#FF6800}{ 0 } = \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 12 }$
$0 = \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 12$
$ $ Move the variable to the left-hand side and change the symbol $ $
$0 \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 12$
$\color{#FF6800}{ 0 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 12$
$ $ Organize the expression $ $
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 12$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ 12 }$
$ $ Change the sign of both sides of the equation $ $
$3 x = - 12$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 12 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo